Short Communication; Medicinal plants in Ubud Monkey Forest in Bali, Indonesia: Diversity, distribution, traditional use and tourism attractiveness - Nyoman Wijana; putuindah rahmawati (Society for Indonesian Biodiversity, 2020)
Abstract. Wijana N, Rahmawati PW. 2020. Short Communication; Medicinal plants in Ubud Monkey Forest in Bali, Indonesia: Diversity, distribution, traditional use and tourism attractiveness. Biodiversitas 21: 2455-2461. The present study attempts to survey and document the medicinal plant diversity found in Ubud Monkey Forest in Bali, Indonesia. The study covers three aspects, namely: ecosystems (vegetation), socio-systems (social) and cultural systems. The population from ecosystem aspects are all plant species that grow in the Ubud?? Monkey Forest. Numerous surveys were conducted to study the distribution pattern of medicinal plants. The purposive samples were used from the aspect of the socio-system, including: community leaders, stakeholders, traditional healers and local community with a total sample of 50 people. The cultural system discussed in this research is Balinese culture. The present study concluded that 28 species of medicinal plants in the Ubud Monkey forest that can be used for traditional medication; medicinal plants in the Monkey Forest are spread in the forest area; these species can be used for internal and external medicine; and various parts of medicinal plant species used for medication are parts of leaves, flowers, fruit, seeds, stems, and roots. The availability of these medicinal plants in Ubud Monkey Forest can be used as an additional attraction for visitors, i.e., for educational tours for students as well as for health and wellness tourism.